Metal Ions Doped-Carbon Dots: Synthetic Approaches, Physicochemical Properties and Their Applications - Dang, Dinh Khoi; Pham, Thanh Tung (Journal of Technical Education Science, 2022)
Carbon dots (CDs) are the most promising members of the carbon family with superior properties such as ultrasmall size, high solubility, low cytotoxicity, and inherent fluorescence endows their potential for diverse applications. There are several discovered methods to improve their properties and the extent of their applications. Possible approaches are doping or surface passivation of CDs to enhance their properties, visible light absorption, and quantum yields by controlling their size, morphology, structure, and band gap energy. As an efficient method to improve the intrinsic properties of carbon dots, doping CDs with heteroatoms such as nonmetallic and metallic atoms has received increasing attention from researchers around the globe. Recently, metal ions doped-carbon dots (M-CDs) have emerged as an important one of nanomaterials with numerous applications. In this paper, we will summarize the state-of-the-art knowledge of M-CDs. The synthetic methods for M-CDs, the novel physicochemical properties originating from the doping of metal ions, and their applications in chemical sensing, biological imaging, phototherapy, optoelectronics, and catalysis will also be highlighted. Furthermore, we will describe challenges in preparing M-CDs and an outlook for their future development.